Microwave spectroscopy of the cold rubidium (n+1)d5/2→ng and nh transitions - Lee J. (2017)
© 2016 American Physical Society. We present an experimental technique that allows us to determine the zero-field intervals between high- states of Rb in a magneto-optical trap, in spite of the fact that we can only control the stray electric field in one direction. The technique is based on measuring a property of the atom that depends on the field, as opposed to its square. This approach allows the determination of the zero-field intervals and the magnitude of the stray field in the uncontrolled perpendicular direction. We use this technique to observe the microwave transitions of rubidium from the (n+1)d5/2 states to the ng and nh states of 27≤n≤30. From the observed microwave transitions, we determine the quantum defects of the ng and nh states. Using the quantum defects of the ng and nh states and the adiabatic core polarization theory, we determine the Rb+ ionic dipole and quadrupole polarizabilities to be αd=9.12(2)a03 and αq=14(3)a05, respectively.